Efektivitas Iklan Layanan Masyarakat - Khairifa, Feni (Komunika, 2023)
Television is the one of communication media that have fluency in society. Besides of giving information, education, and entertainment, television is also always to use for giving conciousness to people about all of currency issue. These are being act by society service advertisement. The research’s purpose is used to find out the answer about is it the society service advertisement was shown by television was being watched by audience and how the understanding’s audince to the society service advertisement. All of the data’s research is taken from research method by using questioner in qustionnaire’s forms. The two of differences research was done to research the audience acceptance of the society service advertisement about the health andthe safety on the roadway. The research’s result is showing that 9 of 10 respondent ever saw the society service advertisement was research by television. However the amount of them who can understand and know well the society service advertisement is still little. Beside of that, some of the watchers television said that the messages in the society service advertisement is still hard to be understood. Therefore, the television has to continuously to playing the society service advertisement and need for taking the steps to making easier in audience’s understanding on messages of the society service advertisement was shown by television.  Keywords: society service advertisement, television